Applied prospect of modern information technology in relation to mountain flood disaster monitoring and early warning system. Issue 7 (3rd October 2017) - He, Yun-Hu; Jiang, Ru-Cheng; Gu, Shi-Xiang
Abstract: The Mountain flood disaster Monitoring and Early Warning (Abbr. MFDMEW) system in China is generating increasing amounts of data as it is developed. Using modern information technology, these data are currently gathered, analyzed, and integrated in an attempt to improve both the level of management and the effciency of the operation. Combined with descriptions of both its data structure and its big-data characteristics ("4V + 1C"), this article analyzes the development trend of MFDMEW system in terms of the information sharing, dynamic early warning model, and standardization; Furthermore, the status of Chinese and international development and practices regarding big-data technology are summarized. Big-data technology, in relation to MFDMEW system, is applied mainly to enhance efficiency and to increase the value of the predictions.